Water Level Monitoring System User Interface Using Node-Red - Hasni, Noorathirah; Saparudin, Faiz Asraf (Progress in Engineering Application and Technology, 2023)
This study addresses the challenges faced by rice farmers in Sungai Balang, Muar Johor, related to water level control in paddy fields, which negatively affects neighboring rice plants and incur additional costs. To tackle this problem, a systematic monitoring system utilizing IoT technologies is proposed. The main objective of this project is to design and implement a user-friendly water level monitoring system for paddy fields, integrating Node-RED, ThingSpeak, and MQTT protocols. Water level sensors are deployed in each paddy plot to continuously detect and monitor water levels, with the collected data transmitted to the cloud-based platform, ThingSpeak, in real-time via MQTT. A web-based interface developed using Node-RED provides owners and the management committee convenient access to the water level data, facilitating effective decision-making and early detection of potential overflow or water shortage situations. The smartphone application generates notifications and alerts to enable timely intervention and prevent crop damage. Through leveraging IoT technologies, this project aims to enhance water management practices, improve productivity, and reduce costs in the paddy farming sector. The proposed water level monitoring system, with its intuitive user interface, allows for real-time monitoring, data analysis, and informed decision-making for farmers and the management committee.